2017
DOI: 10.1080/00325481.2017.1381538
|View full text |Cite
|
Sign up to set email alerts
|

Association between triglyceride/high-density lipoprotein ratio and hearing impairment in a Korean population

Abstract: High TG/HDL-C ratio was associated with hearing impairment in a Korean population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…When mitochondria fail, the vasculature of the inner ear is one of the primary sites of injury, and elevated blood glucose will ultimately cause marginal cell damage and necrosis (40). As previously reported (41,42), HI is associated with increased triglycerides and decreased High-density lipoprotein (HDL). In spite of the fact that the underlying mechanisms of triglycerideinduced HI and HI pathogenesis are still unclear, altered microcirculation in the inner ear may have a profound effect on these conditions.…”
Section: Discussionmentioning
confidence: 93%
“…When mitochondria fail, the vasculature of the inner ear is one of the primary sites of injury, and elevated blood glucose will ultimately cause marginal cell damage and necrosis (40). As previously reported (41,42), HI is associated with increased triglycerides and decreased High-density lipoprotein (HDL). In spite of the fact that the underlying mechanisms of triglycerideinduced HI and HI pathogenesis are still unclear, altered microcirculation in the inner ear may have a profound effect on these conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Decreased nitric oxide production and increased reactive oxygen levels due to dyslipidemia can lead to hearing damage [ 22 , 37 , 38 , 39 ]. Furthermore, HDL was shown to have anti-inflammatory, antioxidant, and anti-apoptotic effects that can attenuate the pathological changes caused by dyslipidemia [ 34 , 40 ] High TG/HDL ratio has been associated with hearing loss [ 23 ] as has low HDL [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study in US adults found that low HDL correlated with hearing loss, with low HDL being most responsible for the correlation between hearing loss and metabolic syndrome. [ 3 ] Two studies in the Korean population reported that low HDL and high TG were highly correlated with hearing loss, [ 11 , 23 ] and one study in a Chinese population reported that hearing loss was positively correlated with low HDL, hyperglycemia, and central obesity [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, well-known HI risk factors in the general population include age [ 9 ], genetics, behavioural factors (e.g., smoking and exercise) [ 10 ], environmental exposures (e.g., noise exposure), health care utilization factors (e.g., immunization and antibiotics), and chronic disorders (e.g., hypertension and diabetes) [ 11 ]. Furthermore, various biomarkers involved in inflammation (such as increased white blood cell (WBC) counts, neutrophil (NE) counts, monocyte (MO) counts, and lymphocyte (LY) counts) and metabolic parameters (such as low-density lipoprotein (LDL) and high-density lipoprotein (HDL)) are also recognized as risk indicators of HI [ 12 ]. Chronic changes in inflammatory status that accompany the ageing process, known as inflammation, may cause or accelerate long-term damage to the hearing system [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Red blood cell distribution width (RDW), a parameter used to classify anaemia, was recently reported to be associated with inflammation and microcirculation disorders [ 14 ]. HDL and LDL have been reported to affect blood supply and thus may potentially influence sudden sensorineural HI [ 12 ]. While several studies have attempted to investigate the relationships between HI and blood inflammation and metabolic parameters, limited studies have used these parameters to predict HI.…”
Section: Introductionmentioning
confidence: 99%